Representations of Longing in Maher Zain's Qolbi Fi Madinah: A Roland Barthes Semiotic Analysis - Muhammad Daffa Fibril Erlangga; Maman Abdul Djaliel; Asep Supianudin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study examines the representation of spiritual longing (kerinduan) in the lyrics of the song Qolbi Fi Madinah by Maher Zain through Roland Barthes' semiotic framework of denotation, connotation, and myth. Religious songs increasingly function as media through which contemporary Muslim spirituality is symbolically expressed, particularly longing toward sacred spaces and the Prophet Muhammad. Using a qualitative descriptive-analytical method, eight lyrical units were identified as primary data and analyzed through documentation and library research techniques. The findings indicate that at the denotative level, the lyrics literally express the heart's presence in Madinah, tears of longing, and direct address to the beloved. At the connotative level, these expressions are elaborated into emotional and spiritual meanings such as intense love (‘ishq), inner tranquility, and spiritual ascent. At the mythical level, the lyrics naturalize the belief that longing for Madinah and the Prophet constitutes an ideal form of piety, positioning sacred space as the ultimate locus of spiritual serenity. This study contributes to Arabic literature studies by demonstrating how popular religious songs construct religious ideology through poetic and symbolic language.